Role of Prophylactic Administration of Calcium Gluconate in the Early Post Operative Period after Total Thyroidectomy at Surgical department Ayub Teaching Hospital Abbottabad (Medical Forum Monthly, 2023)
Objective: To assess the role of prophylactic administration of calcium gluconate in early postoperative patients after total thyroidectomy.Study Design: Prospective studyPlace and Duration of Study: This study was conducted at the Surgery Department, Ayub Teaching Hospital, Abbottabad from January 2022 to June 2022.Materials and Methods: A total of 72 patients were included in the study through the purposive sampling technique, but the participants were divided into two groups randomly. One was group 1 who had received prophylactic calcium gluconate while group 2 had not. All the data were collected from the patient’s assessment records and laboratory reports and were analyzed by using the latest version of SPSS 24.Results: A total of 72 patients were included in the study through the purposive sampling technique, but the participants were divided into two groups randomly. The mean age of Group 1 was 38.42 ± 9.35, while Group 2 had 39.57±10.7 years. There was male 13 (36.11 %) and female 23 (63.88) in Group 1, furthermore, in Group 2 there were mal 17 (47.22 %) and female 19 (52.77 %). Multinodular goiter was the most common reason (17 (47.22%)) for surgery in both of the groups equally. The mean hospital stay in Group 1 was 2.4± 0.8 while in Group was 3±1.3 having a p-value of 0.005. Consequently, the level of Ca+ after 12 and 24 hours in Group 1 was 8.9±0.4 and 8.9±0.5 respectively, however, in Group 2 was 8.2±0.3 and 8.4±0.2. paresthesia in Group 1 after 12 and 24 hours 2 (5%) and 1 (2.7 %) was accordingly, similarly, in Group 2, 5 (13.8 %) and 3 (8.3 %) accordingly. Comparably, the intravenous calcium 1 (2.7 %) in Group 1 and Group 2, 4 (11.11 %).Conclusion: The present study concluded that the prophylactic use of calcium gluconate in the patients who underwent a total thyroidectomy had a more prominent effect on the patient’s hospital stay as well as on the postoperative serum calcium. Those in Group 1 who had received calcium had shorter hospital stays and a higher level of serum as well as requirements of IV calcium as compared to others in Group 2.